European dimension of the constitution - Introduction - Bisztyga, Andrzej (1964- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Constitutional law is the only discipline of law containing a group of norms with the highest legal force, i.e., the norms of the Constitution. The state constitution is the keystone of the national law system and its provisions, including those relating to European integration, determine the content of legal disciplines other than constitutional law. The supra-disciplinary nature of the research problem addressed attracted the attention of researchers representing legal disciplines other than constitutional law and European law.
Keywords: konstytucja; prawo krajowe a prawo Unii Europejskiej; prawo pierwotne Unii Europejskiej; prawo porównawcze; Unia Europejska